Impact of High-Volume Fat Removal on Physical and Psychological Parameters in Obese and Overweight Females - Muhammad Usman, Romana Mehwish, Amna Riaz, Shahid Mukhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the physiological and psychological changes following large-volume liposuction in overweight and obese women. Methods: This prospective study was conducted at plastic surgery department of Bakhtawar Amin Medical & Dental College, Multan, from June 2022 to June 2023, and included 50 overweight and obese female patients undergoing large-volume liposuction. Baseline demographic data, weight, body mass index (BMI), and blood pressure were recorded preoperatively and reassessed postoperatively. Psychological assessment was performed using the Hospital Anxiety and Depression Scale (HADS) and body image scores, measured preoperatively and at 1 and 3 months postoperatively. Statistical analysis was carried out to assess changes over time. Results: The mean age of participants was 38.4 ± 7.6 years, with a mean preoperative BMI of 33.8 ± 3.9 kg/m² and weight of 87.2 ± 11.5 kg. Following liposuction, significant reductions were observed in weight (p<0.001) and BMI (p<0.001). Systolic and diastolic blood pressures also decreased significantly postoperatively (p=0.01 and p=0.02, respectively), along with a reduction in heart rate (p=0.01). Psychologically, patients demonstrated a significant improvement in HADS-anxiety (p<0.001) and HADS-depression scores (p<0.001) across follow-up intervals. Body image scores showed positive correlation with total aspirated fat volume (r=0.42, p=0.01). Conclusion: Large-volume liposuction in overweight and obese women leads to significant improvements in both physiological parameters, such as weight, BMI, and blood pressure, and psychological well-being, including anxiety, depression, and body image. These findings suggest that liposuction may play a beneficial role beyond aesthetics, contributing to overall health and quality of life in obese women. Keywords: Liposuction; Obesity; Overweight women; Body mass index; Psychological well-being; Body image;